Laparoscopic partial nephrectomy for the management of large renal tumors: Experience at a tertiary care hospital - Truong TT; Le QH; Le HQ; Nguyen VT; Giang NP; Trang TM (Journal of Medical and Scientific Research)
Background: Laparoscopic partial nephrectomy is increasingly replacing open surgery as a standard, yet technically demanding, treatment for kidney tumors. The study aimed to evaluate some characteristics of large kidney tumors and results of retroperitoneal laparoscopic partial nephrectomy for large kidney tumors at a provincial general hospital.